THE EXPRESSIONS OF CORRECTIVE FEEDBACK IN SECOND LANGUAGE CLASSROOM - Sulistyani, Sulistyani (English Teaching Journal, 2014)
This study aims to review the teacherâs expressions which constitute teacherâs corrective feedbacks (CFs) in oral production and examine the ways the teachers expression revealing teacherâs CFs. The data are in the forms of teachers utterances obtained from four research articles. The result shows that teacher expressions whichÂ  constitute CFs cover explicit correction, recast, clarification request, metalinguistic, elicitation, and repetition. While the ways which reveal teacherâs CFs are found to be reduction, negation, andÂ  expansion. The area to be corrected commonly involves phonological, grammatical, and lexical errors. So, it can be concluded that in a second language classroom instruction, teacherâs CFs expressions lead learners erroneous utterances to be resolved because by saying "Sorry?" (clarification request), a teacher implicitly asks a language learner to reformulate what he has just been said which is usually called repair. Thus, it implies that the teacherâs CFs expressions in a second language classroom instruction are facilitative to resolve learners problematic linguistic accuracy. In Indonesia, where English is used as foreign language, CFs are important to be practiced. Therefore, CFâs expressions are necessary to be introduced as a model to practice for the improvement of the linguistic competence especially in English speaking as it is assumed that excellence in speaking is expected to increase Indonesian human capital particularly in global competition and international communication.